Toxic exposures : mustard gas and the health consequences of World War II in the United States - Smith, Susan Lynn, 1960- (Critical Issues in Health and Medicine Ser., 2017)
Toxic Exposures tells the shocking story of how the United States and its allies intentionally subjected thousands of their own servicemen to mustard gas as part of their preparation for chemical warfare. Drawing from once-classified government records, military reports, scientists' papers, and veterans' testimony, Susan L. Smith assesses the poisonous legacies of these experiments, including scientific racism and environmental degradation. In addition, she reveals their surprising impact on the origins of chemotherapy as cancer treatment and the development of veterans' rights movements.